National Health Service Bill : Summary of proposed new service (London : His Majesty's Stationery Office)
1946-03 1946 1940s 19 pages 6 be settled by subsequent regulations, existing debts and liabilities attaching to the voluntary hospitals concerned. He is then to apportion the capital value of the Fund among the several Regional Hospital Boards and, as it were, to earmark to each a portion. The income of each portion will then pass automatically to each Board and it will be free to use it as it wishes, within such general conditions as may be prescribed. Any Board will be able also at any time to draw on its portion of the capital for any purpose which the Minister approves. 17. The Boards — and the Boards of Governors of teaching hospitals — are fully able under the Bill to receive gifts or legacies, and to hold any property on trust, for any purposes connected with the hospital or health services. 18. The detailed arrangements affecting the new Hospital Endowment Fund, its apportionment and administration, are left to be settled by later statutory regulations. Hospital administration 19. The Minister is to entrust the future administration of all the hospitals (other than teaching hospitals) to Regional Hospital Boards to be set up under the Bill for such hospital service regions of the country as he will prescribe — each region being such that its services can conveniently be associated with a university medical school. There will probably be between sixteen and twenty of these regions. 20. Each Board will be composed of people chosen and appointed by the Minister for their individual suitability for the task, but before making the appointments the Minister is to consult any university with a medical school in the region, bodies representative of the medical profession, the local health authorities of the area, and others concerned including, initially, those with experience of the voluntary hospital system. The Boards are to include some members with experience of the mental health services. 21. Each Board is required by the Bill to appoint, in accordance with a scheme approved by the Minister, local Hospital Management Committees, one for each large hospital or related group of hospitals forming a reasonably self-contained hospital service unit. Each of these Management Committees will contain members appointed after consulting the major local authorities in its area, the Executive Councils for the general practitioner services in its area, the senior medical and dental staff of the hospitals concerned, and others, including those with experience in voluntary hospitals. 22. It is to be the duty of the Regional Boards, within the scope of general regulations and such particular directions as the Minister may give, to undertake on his behalf the general administration of the hospital and specialist services in their regions. With the Minister, and in collaboration with the teaching hospitals, each Board will plan, and execute the plan for, a co-ordinated hospital and specialist service for its region. 23. It is to be the duty of the Management Committees to carry out day-to-day management of the particular hospitals under their control — within such limits as are to be prescribed by the Minister. They are to be the local managing bodies on the spot, and they will, for example, appoint nursing and other general staff (appointing them as employees of the Regional Boards). They will be able, as required, to set up small house-committees for any individual hospitals within their care. 24. It is the object that the Regional Boards, with their local Management Committees, shall enjoy a high degree of independence and autonomy within their own fields. Their use of existing voluntary hospital endowments has 292/847/4/115